Предмет: Алгебра,
автор: dfsdfsdfrfgrefrefce
x*(2-x)/2+x(3+2x)/3=1
Ответы
Автор ответа:
0
x*(2-x)/2+x(3+2x)/3=1
2x-x^2/2+3x+2x^2/3=1
приводим к общему знаменателю
(2x-x^2)*3/2+(3x+2x^2)*2/3=1
(6x-3x^2+6x+4x^2)/6=1
x^2+12x=6
x^2+12x-6=0
2x-x^2/2+3x+2x^2/3=1
приводим к общему знаменателю
(2x-x^2)*3/2+(3x+2x^2)*2/3=1
(6x-3x^2+6x+4x^2)/6=1
x^2+12x=6
x^2+12x-6=0
Похожие вопросы
Предмет: Английский язык,
автор: devichenkomilana
Предмет: География,
автор: shlikerblack
Предмет: Информатика,
автор: Аноним
Предмет: Математика,
автор: ArtemStroev